Dinâmica populacional do camarão Alpheus brasileiro Anker, 2012 (Decapoda: Caridea: Alpheidae) em Cananéia, extremo sul do estado de São Paulo, Brasil - Pescinelli, Régis Augusto [UNESP] (2015)
The aim of this study was to investigate the relative growth, the morphological and functional sexual maturity, the spawning period, recruitment, sex ratio, heterosexual pairing and fertility of the snapping shrimp Alpheus brasileiro. Shrimps were captured manually from March 2013 to January 2014 in the intertidal estuarine zone of Cananéia, SP. Individuals were identified according to sex and measured in relation to the carapace length (CL), propodus cheliped length (PCL), propodus cheliped width (PQW), propodus cheliped height (PQH), length of second abdominal pleura (PL), internal appendix length (IAL) and male appendage length (MAL). During the studied period, 186 individuals were collected, 92 males and 94 females. The relationships that best evidencied changes in growth rate between juveniles and adults were CPQ vs. CC and CP vs. DC. These relationships were used to estimate the morphological sexual maturity for males and females, which were 4.70 and 4.77 mm CW, respectively. The functional maturity was calculated in 4.80 mm CW. The reproductive period was characterized as seasonal continuous, as well as the recruitment, which is considered as an exception to the expected pattern for tropical and subtropical species. There was no statistically significant difference in sex ratio (M: F) (p> 0.05). This fact is probably due to the pairing behavior, in which the pair formation occurs in gonocoric species and favors equal distribution between males and females. During the study 42 pairs (male and female) were captured. Couples were present in the population in all months of sampling. Territorial behavior is intense and it is commonly found in Alpheidae shrimp, so the pairing strategy can ensure survival and reproductive success. The mean fertility calculated was 148.53 ± 93.37, related to 28 females. There was a positive correlation between the number of eggs and the carapace, Spearman correlation (p<0.05), highlighting a ...